Influence of Meteorological Conditions on Artificial Ice Reservoir (Icestupa) Evolution - Balasubramanian, Suryanarayanan; Hoelzle, Martin; Lehning, Michael; Bolibar, Jordi; Wangchuk, Sonam; Oerlemans, Johannes; Keller, Felix (Frontiers in Earth Science, 2022)
Mountain communities in Ladakh, India have been using Artificial Ice Reservoirs (AIRs) for additional irrigation water supply. However, there is a large variability associated with this water supply due to the local weather influences at the chosen location. This study compared the ice volume evolution of three AIRs built in Ladakh, India and Guttannen, Switzerland using a surface energy balance model. Model input consisted of meteorological data in conjunction with fountain discharge rate (mass input of an AIR). Model calibration and validation were completed using ice volume and surface area measurements taken from several drone surveys. The model achieved an RMSE within 18 % of the maximum ice volume with the ice volume observations for all the AIRs. The location in Ladakh had a maximum ice volume around four times larger compared to the Guttannen site. However, the corresponding water losses for all the AIRs were more than three-quarters of the total fountain discharge due to high fountain wastewater. Drier and colder locations in relatively cloud-free regions are expected to produce AIRs with a faster freezing rate and slower melting rate. This is a promising result for dry mountain regions, where AIR technology could provide a relatively affordable and sustainable strategy to mitigate climate change induced water stress.